A case developing minimal change disease during the course of IgG4-related disease. Issue 4 (4th July 2017) - Yamada, Kazunori; Zoshima, Takeshi; Ito, Kiyoaki; Mizushima, Ichiro; Hara, Satoshi; Horita, Shigeto; Nuka, Hiromi; Hamano, Ryoko; Fujii, Hiroshi; Yamagishi, Masakazu; Kawano, Mitsuhiro
Abstract : We describe a 66-year-old male with immunoglobulin G4-related disease (IgG4-RD) presenting with minimal change disease (MCD). Three years prior to this admission, the patient had been diagnosed with IgG4-RD. The development of sudden massive proteinuria (4+; 16.7 g/gCr) with a weight gain of 8 kg within a two-week period was noted, and nephrotic syndrome was suspected. The patient's serum IgG4 level did not increase and hypocomplementemia was not found. A renal biopsy showed no cellular infiltration in the renal interstitium, and no spiking or bubbling was found on periodic acid methenamine silver staining. On electron microscopy, foot process effacement was seen, but no subepithelial electron-dense deposits were found. The patient was diagnosed with MCD. Ten days after starting prednisolone (60 mg/day), proteinuria was negative. Since IgG4-RD and MCD share a T-helper 2-dominant immunoreaction, the development of MCD in IgG4-RD patients may reflect more than a mere coincidence.